Cell structure imaging with bright and homogeneous nanometric light source. Issue 4 (8th June 2016) - Fukuta, Masahiro; Ono, Atsushi; Nawa, Yasunori; Inami, Wataru; Shen, Lin; Kawata, Yoshimasa; Terekawa, Susumu
Abstract : Label‐free optical nano‐imaging of dendritic structures and intracellular granules in biological cells is demonstrated using a bright and homogeneous nanometric light source. The optical nanometric light source is excited using a focused electron beam. A zinc oxide (ZnO) luminescent thin film was fabricated by atomic layer deposition (ALD) to produce the nanoscale light source. The ZnO film formed by ALD emitted the bright, homogeneous light, unlike that deposited by another method. The dendritic structures of label‐free macrophage receptor with collagenous structure‐expressing CHO cells were clearly visualized below the diffraction limit. The inner fiber structure was observed with 120 nm spatial resolution. Because the bright homogeneous emission from the ZnO film suppresses the background noise, the signal‐to‐noise ratio (SNR) for the imaging results was greater than 10. The ALD method helps achieve an electron beam excitation assisted microscope with high spatial resolution and high SNR. Abstract : Label‐free optical nano‐imaging of dendritic structures and intracellular granules in biological cells is demonstrated using a bright and homogeneous nanometric light source. The optical nanometric light source is excited using a focused electron beam. A ZnO luminescent thin film was fabricated by atomic layer deposition (ALD) to produce the nanoscale light source. The ALD method helps achieve an electron beam excitation assisted microscope with high spatial resolution and high SNR.